Behind the fertility–education nexus: what triggered the French development process?. (13th June 2017) - Diebolt, Claude; Menard, Audrey-Rose; Perrin, Faustine
Abstract: The education–fertility relationship is a central element of the models explaining the transition to sustained economic growth. But many determinants of this relationship have not yet received more systematic attention. In this paper, we apply a three-stages least-squares estimator on French county-level data, including newly collected data, to better understand the causal effects running from education to fertility, and vice versa. We put forward the hypothesis that a decrease in fertility was strongly associated with greater schooling in France during the nineteenth century. Besides, we emphasize the relevance of taking account of gender equality and family organization when explaining the education–fertility relationship.